An exploration of the effect of market-driven journalism on The Monitor newspaper's editorial content - Agaba, Grace Rwomushana (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
The media today are under pressure from various fronts including governments, businesses as well as cultural interests. In the developed world, this pressure that led to the emergence of a new form of journalism that puts the demands of the market at the forefront. This commercial oriented journalism gives priority to articles that attract mass audiences like entertainment while it downplays information that promotes debates that is necessary for citizens to be able to have a voice on the issues that affect them. And since participation and discussion are cornerstones of a democratic process, market-driven journalism undermines democracy because it narrows down the forum for debate. As a result, active citizens are turned into passive observers in society. Although several studies about this phenomenon have been done in the western world, the same is happening in Africa because the media face similar challenges as in the West; challenges of globalisation and media conglomeration facilitated by the rapid advancing technology. This study, which is informed by political economy and market-driven journalism theories, notes that the media in Uganda are also faced with these challenges. The study is focused on Uganda's only independent newspaper, The Monitor. The findings indicate that market-driven journalism is taking root at the expense of journalism that promotes citizenship and debate such as political reporting and opinions. For example, there has been an increase of entertainment, sports and supplement articles in The Monitor as compared to declining political reporting and opinions. More so, investigative reporting has dwindled over the years at the expense of increasing use of press releases. This is because entertainment and sports articles can attract big audiences that the newspaper needs to sell to advertisers. Advertisers are important because they provide financial support to the newspaper. However, in a country where democracy is in its formative stages, public information is necessary not only for citizens to make informed decisions but also to spur economic as well as social development.
Keywords: Monitor (Uganda); Journalism -- Political aspects -- Uganda; Journalism, Commercial -- Uganda; Mass media and public opinion -- Uganda; Mass media -- Political aspects -- Uganda; Freedom of the press -- Uganda; Press and politics -- Uganda; Journalism -- Social aspects